Atitudes do enfermeiro frente ao processo de enfermagem - Silva, Cristiane Rodrigues (2015)
Objectives: To analyze the Nurse’s position on the Nursing Process (NP) at a University Hospital. Method: This is an analytical transversal study. The sample was composed of 141 Nurses. The data collection was done using the Positions on Nursing Process (PNP) tool. The total PNP score could vary between 20 and 140. The score on the different items of the PNP were interpreted as: most unfavorable (mean score ≤4.5); favorable (mean score 4.6-5.4); and strongly favorable (mean score ≤5.5). Statistical analysis: Descriptive statistics and associations, conducted by Pearson's chi-square test. P <0.05 was considered significant. Results: The general scores varied between 73 and 138. The PNP total mean score was 113.29 (SD=15.33). The Nurses perceive the NP as significant, valuable, positive, intelligent, valid, meaningful, relevant, rewarding, convenient, acceptable, good, and important; hence showing attitudes that are strongly favorable to the NP. The score obtained in the analysis of the items that incorporate the adjectives: clear, agreeable, strong, comfortable, realist, and enabling presented scores between 4.6 and 5.4; hence, these have classified the Nurses’ position on these attributes as favorable to the NP. Only the analysis of the items that include the adjectives difficult and routine rendered a mean score of ≤4.5, showing attitudes that are more unfavorable to the NP. Still, presenting no satisfaction with the career, satisfaction with the work station and having previous knowledge of the Nursing diagnoses are variables related to the attitudes that are favorable to the NP. Conclusion: This study allows us to conclude that the Nurses at the studied institution have favorable attitudes on the NP. The variables related to the favorable attitudes are: presenting satisfaction with the career, satisfaction with the work station and having previous knowledge of the Nursing diagnosis.